Antibodies to SARS-CoV-2 in dogs and cats, USA. Issue 1 (1st January 2021) - Barua, Subarna; Hoque, Monirul; Adekanmbi, Folasade; Kelly, Patrick; Jenkins-Moore, Melinda; Torchetti, Mia Kim; Chenoweth, Kelly; Wood, Theresa; Wang, Chengming
ABSTRACT: To provide more complete data on SARS-CoV-2 infections in dogs and cats in the U.S., we conducted a serosurvey on convenience serum samples from dogs ( n =1336) and cats ( n =956) collected from 48 states of the USA in 2020. An ELISA targeting the antibody against nucleocapsid identified eleven positive and two doubtful samples in cats, and five positive and five doubtful samples in dogs. A surrogate neutralization assay detecting antibodies blocking the attachment of the spike protein to ACE2 was positive with three of the ELISA positive and doubtful samples, and one of 463 randomly selected ELISA negative samples. These four positive samples were confirmed by SARS-CoV-2 virus neutralization testing. All were from cats, in New York, Florida, and New Jersey ( n =2). The serosurvey results, one of the largest yet completed on dogs and cats globally, support the OIE and CDC positions that currently there is no evidence that pets play a role in the spread of SARS CoV-2 in humans.